Elucidation of the Vicarious Nucleophilic Substitution of Hydrogen Mechanism via Studies of Competition between Substitution of Hydrogen, Deuterium, and Fluorine - Ma̧kosza, Mieczysław; Lemek, Tadeusz; Kwast, Andrzej; Terrier, François (Journal of organic chemistry, 2002)
Relations of rates of the vicarious nucleophilic substitution of hydrogen (VNS) and SNAr substitution of fluorine in 2-fluoronitrobenzenes with chloroalkyl aryl sulfone carbanions were determined from competitive experiments carried out at various concentrations of base. The observed dependence of the VNS/SNAr rate ratio on the base concentration confirmed the two-step mechanism of the VNS, which consists of reversible formation of σH adducts of the α-chlorocarbanion to nitroarene, followed by base-induced β-elimination of HCl. It was also evidenced that both of these processes can be the rate-limiting steps:  the β-elimination at low base concentration and the nucleophilic addition at high base concentration. Consistent with that conclusion is the finding that the kinetic isotope effect in the VNS reaction decreases from 4.2 (a value typical of a primary KIE) to 0.8 (a value typical of a secondary KIE) with increasing base concentration. Also reported is our discovery that the SNAr substitution of the 2-fluoronitrobenzenes studied in this work was subject to base catalysis under some of the experimental conditions employed in our competitive experiments.